2016
DOI: 10.1002/hep.28754
|View full text |Cite
|
Sign up to set email alerts
|

Bone marrow stem cells and their niche components are adversely affected in advanced cirrhosis of the liver

Abstract: Increasing severity of cirrhosis causes derangement of the hematopoietic niche and loss of HSCs, contributing to the hematological and immunological dysfunctions and reduced potential for regeneration; restoring BM functions could provide new therapeutic options in cirrhosis. (Hepatology 2016;64:1273-1288).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

6
48
1
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 53 publications
(64 citation statements)
references
References 52 publications
6
48
1
1
Order By: Relevance
“…This suggests that a healthy cellular BM is a pre‐requisite for effective stem cell mobilization therapy and BM paralysis in advanced liver disease might be responsible for their non‐response to growth factor therapy. Advanced cirrhosis is known to have deleterious effect on BM HSCs and may be responsible for ineffective mobilizable HSC pool from the BM.…”
Section: Discussionmentioning
confidence: 99%
“…This suggests that a healthy cellular BM is a pre‐requisite for effective stem cell mobilization therapy and BM paralysis in advanced liver disease might be responsible for their non‐response to growth factor therapy. Advanced cirrhosis is known to have deleterious effect on BM HSCs and may be responsible for ineffective mobilizable HSC pool from the BM.…”
Section: Discussionmentioning
confidence: 99%
“…The severe inflammatory condition present in AH could also alter this phenomenon. A reduced potential of regeneration for bone marrow stem cells from patients with cirrhosis was also recently described and correlated with the severity of the liver disease assessed by prognostic factors [24]. Another hypothesis is that the bone marrow stimulus in our study (5-day GCSF stimulation followed by one single injection of stem cells in the hepatic artery) was not sufficient to enhance regeneration.…”
Section: Discussionmentioning
confidence: 49%
“…At present, splenic platelet sequestration is considered to be the major cause of thrombocytopenia in cirrhotic patients,46 while immunological processes, chronic HCV infection, and a decrease in hematopoietic growth factors can also contribute to it 7. Studies have also shown that bone marrow function is suppressed in advanced cirrhosis and the potential for regeneration declines, and this contributes significantly to hematological abnormalities in patients 8. Thrombocytopenia is considered a major risk factor for bleeding events; however, in recent years, some researchers have argued that a “rebalance” would be established in patients with chronic liver disease9 as coagulation inhibiting factors decrease concomitantly when clotting factors decline 10.…”
Section: Discussionmentioning
confidence: 99%
“…But in the case of the patient described in this study, platelet count declined much more sharply than generally observed and failed to improve after platelet transfusion and supportive treatment. While input platelets are likely to have been destroyed in the spleen, decreased bone marrow compensatory function due to long-term cirrhosis and thrombocytopenia must also be considered as this may lead to deficient hematopoiesis and poorer tolerance of radiotherapy 8. Therefore, for patients with liver cirrhosis and thrombocytopenia, bone marrow function may also be defective in addition to hypersplenism.…”
Section: Discussionmentioning
confidence: 99%